2020
DOI: 10.1007/s00380-020-01713-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of pre-existing medical comorbidity in Takotsubo cardiomyopathy

Abstract: Takotsubo cardiomyopathy (TC) is associated with significant short-term morbidity and mortality. Several risk factors for poor outcomes have been identified; however, the prognostic implications of pre-existing comorbidity in TC are poorly delineated. We sought to assess the association of aggregate pre-existing comorbidity with short-term outcomes in TC. We performed a retrospective observational study of adult subjects diagnosed with TC at two academic tertiary care hospitals between 2005 and 2018. Overall b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…The Charlson score is an indicator of the degree of comorbidity at the time of admission. A study reported that TTS due to physical stress was associated with a higher Charlson score 20. We showed that the Charlson score might be useful in predicting TTS severity.…”
Section: Discussionmentioning
confidence: 56%
“…The Charlson score is an indicator of the degree of comorbidity at the time of admission. A study reported that TTS due to physical stress was associated with a higher Charlson score 20. We showed that the Charlson score might be useful in predicting TTS severity.…”
Section: Discussionmentioning
confidence: 56%
“…28 Other studies suggest that age is not associated with shortterm mortality in TCM patients (Table 2). 18,19,23,27,38,63,69,70 After a multivariable logistic regression analysis, Cammann et al found no significant difference among different age groups in in-hospital mortality (age 51-74 years old as reference, ≤50 years old, P = 0.14; ≥75 years old, P = 0.75) or 60 day mortality (P = 0.16). 27 In a univariate meta-regression analysis of 54 studies with 4679 TCM patients, in-hospital mortality in each study was not associated with age (P = 0.67, coefficient: 0.002, 95% CI 0.000-0.004), although the in-hospital mortality rate had wide heterogeneity (I 2 = 78%).…”
Section: Agementioning
confidence: 99%
“…A prospective study of 1750 TCM patients in the International Takotsubo Registry noted that about 36% of TCM cases were triggered by specific physical activities, 27.7% was triggered by emotion, 2.8% were triggered by both physical and emotional activities, and 28.5% of cases had no identifiable trigger. 8 Many studies show that physical triggers are associated with poor short-term 8,70,80,84,85 42 A study of 939 TCM patients from the Spanish National Registry on Takotsubo Syndrome used multiple Cox regression to show that patients with physical triggers (HR 3.073, 95% CI 1.758-4.302) and those with no identifiable trigger (HR 1.913, 95% CI 1.003-3.649) had a higher 5 year mortality rate than patients with emotional triggers group. 55 Emotional triggers, on the other hand, predict better shortterm 8,27 and long-term 44,47,56 TCM outcomes (Table 4).…”
Section: Trigger Eventsmentioning
confidence: 99%
See 2 more Smart Citations